THE POSITIVE EXPERIENCE OF FRANCE REGARDING THE SYSTEMATIZATION OF SOCIAL LEGISLATION: DIRECT BORROWING INTO NATIONAL SOCIAL LEGISLATION - O. P., Saynetsʹkyy (Київський національний університет імені Тараса Шевченка, 2022)
In the article the specifics of French social legislation are analyzed. The peculiarities of normative legal acts in the field of social protection are characterized. The content of each of them is outlined. Positive aspects of legal regulation of social protection in France are emphasized. Directions for borrowing French experience into national social legislation are indicated. The essence of each of the legislative proposals is substantiated.

У статті проаналізовано специфіку соціального законодавства Франції. Охарактеризовано особливості нормативно-правових актів у сфері соціального захисту. Окреслено зміст кожного з них. Наголошено на позитивних аспектах правового регулювання соціального захисту у Франції. Наведено напрями запозичення досвіду Франції у національне соціальне законодавство. Обгрунтовано сутність кожної із законодавчих пропозицій.
ПОЗИТИВНИЙ ДОСВІД ФРАНЦІЇ ЩОДО СИСТЕМАТИЗАЦІЇ СОЦІАЛЬНОГО ЗАКОНОДАВСТВА: НАПРЯМИ ЗАПОЗИЧЕННЯ У НАЦІОНАЛЬНЕ СОЦІАЛЬНЕ ЗАКОНОДАВСТВО
Keywords: social legislation; social rights; law; systematization of legislation; social standards; France.; соціальне законодавство; соціальні права; право; систематизація законодавства; соціальні стандарти; Франція.